Analisis Penerapan Metode Full Costing Penentu Harga Pokok Produk - Qur'an, Nur Azmil; Oshan N., Frudiaz; Bagus, Riszal; Jakaria, Ribangun Bambang (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2024)
Production costs owned by each company are certain to increase along with the increase in the amount of demand for finished products in the market. However, the increase in the number of requests for finished products is not proportional to the level of profit generated, making it difficult for companies to control cast flow, therefore allocating costs, and determining the amount of costs becomes something important in order to reduce the cost of production per unit. The purpose of this study is to determine the amount of cost allocation used to determine the cost of goods manufactured to obtain the level of effectiveness and efficiency of the company in order to achieve ideal profits. The method used is the full costing method. The Full Costing method provides a comprehensive overview of production costs, including direct and indirect costs, and provides information relevant to the company's strategic decision making. The results showed that the application of the Full Costing method provides a more comprehensive picture of production costs, so that the company is able to identify more precisely the cost of goods. So that the company is able to increase efficiency, optimize profitability in determining the cost of goods.